Polysulfone gas separation hollow fiber membranes with enhanced selectivity - Ismail, A. F. (Elsevier Science B.V., 1998)
A recent paper dealt with the production of poly- sulfone hollow fiber membranes for gas separation [1]. It was suggested that increased shear during extrusion increases molecular orientation and, in turn, heightens selectivity. Molecular orientation in the membrane active layer was measured by infrared spectroscopy and gas permeation properties (permeability and selectivity) were evaluated using pure carbon dioxide and methane